Enacting Space in Virtual Reality: A Comparison Between Money’s Road Map Test and Its Virtual Version - Morganti, Francesca (Frontiers in Psychology, 2018)
In the field of spatial cognition research the reciprocal relationship between perception and action that underlies spatial orientation was recently investigated. Moreover, the equivalence between creating a cognitive map from the exploration of a not simulated environment, from the use of an allocentric (survey-like) sketched map, and from the interaction with egocentric (route-like) 3D virtual environments, is generally assumed. To understand if different embodied affordances could provide different spatial knowledge organization in wayfinding, the same group of 61 healthy subjects experienced both the classical version of the Money’s Road Map test (M-RMT) and a virtual reality version of the same test (VR-RMT). The M-RMT requires a mental imagery right/left turning to explore a stylized city provided in a survey perspective. The VR-RMT is a 3D version of the same environment through which participants can actively navigate by choosing right/left directions in a route perspective. The results showed that the different embodiments afforded by the two environments and the increasing complexity in turn types provides different spatial outcomes. Results were discussed according to the sensorimotor coupling theory provided from the enactive cognition approach.